Rhodium(I) Complexes of N‐Aryl‐Substituted Mono‐ and Bis(amidinates) Derived from Their Alkali Metal Salts. Issue 26 (14th June 2018) - Moos, Eric M. B.; González‐Gallardo, Sandra; Radius, Michael; Breher, Frank
Abstract : The synthesis and characterization of several rhodium(I) complexes of amidinate and linker‐bridged bis(amidinate) ligands are presented. The amidinate ligands for the mononuclear complexes CH3 C(NMes)2 Rh(cod) (1 ), CH3 C(NDipp)2 Rh(cod) (2 ), and HCCC(NDipp)2 Rh(cod) (3 ) (cod = 1, 5‐cyclooctadiene) were synthesized by reacting the corresponding organometallic precursor [Rh(cod)Cl]2 with the alkali metal amidinates CH3 C(NR)2 LiL1Li (R = Mes = 2, 4, 6‐Me3 C6 H2 ) andL2Li (R = Dipp = 2, 6‐ i Pr2 C6 H3 ). Analogously, the alkynyl‐functionalized sodium amidinate (HCCC(NDipp)2 Na· 2DME, L3Na ) could be further deprotonated and reacted with carbodiimine to form the alkyne‐bridged bis(amidinate) CCC(NDipp)2 Na(thf)2 (L4Na ), which serves as suitable starting material for the synthesis of CCC(NDipp)2 Rh(cod)2 (4 ). The bis(amidinate) ligands for the corresponding para ‐ (5 ) and meta ‐ (6 ) phenylene‐bridged complexes p ‐/ m ‐C6 H4 C(NMes)2 Rh(cod)2 were accessible through the reaction of phthalic acids with trimethylsilyl polyphosphate and mesitylamine and subsequent deprotonation of the obtained amidines. Tetramesityl oxalamidinate was used to synthesize the dinuclear complex C(NMes)2 Rh(cod)2 (7 ) and its carbonylation product C(NMes)2 Rh(CO)2 2 (8 ). All compounds under study were fully characterized by various spectroscopic methods. In particular the alkali metal salt of the linker‐bridged bis(amidinate)L5Na forms a one‐dimensional coordination polymer in the solid state. Reaction ofL5Na andL6Na with [Rh(cod)Cl]2 leads to dinuclear complexes in which the metal–metal distance can be adjusted, enabling us to study their reactivity, including possible cooperative effects in catalysis. Abstract : The first mono‐ and dinuclear rhodium(I) complexes based on amidinates, oxalamidinates, and linker‐bridged bis(amidinates) are reported. The compounds were obtained by salt metathesis reactions of the alkali metal salts of the chelating N donor ligands and have been fully characterized by various methods.